Development of Literacy and Numeracy-Based Assessment Instruments for Madrasah Ibtidaiyah Teacher Education Students - Adriyani, Zuanita; Faqih, Muhammad Izzatul; Kharirroh; Malik, Muh Syauqi (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to develop a good literacy and numeracy-based assessment instrument and the implementation of instrument of the assessment is expected to measure the literacy and numeracy skills of Madrasah Ibtidaiyah Teacher Education UIN Walisongo students. The development procedure in this study adopts the Cennamo and Kalk development reseachr program (R&D) model with steps (1) defining phase, which includes literature study and preliminary observation; (2) the planning phase in the form of the preparation of 30 questions of literacy and numeracy-based assessment instruments; (3) the demonstration phase in the form of a theoretical test of the validity of the question by the expert; (4) the development phase in the form of improving questions based on validators' suggestions and conducting question implemented to number of 35 students to determine empirically valid questions; and (5) the phase of presenting theoretically and empirically valid question instruments as many as 19 questions on a broader scale with 42 students and determining the level of literacy and numeracy skills of students. The selected sample population was students of Madrasah Ibtidaiyah Teacher Education UIN Walisongo Semarang, third-semester class of 2020/2021. Sampling is carried out by purposive sampling technique. The result concludes that the assessment instrument developed meets the criteria of feasible and valid theoretically and empirically. The literacy and numeracy skills of PGMI UIN Walsiongo students in the low category are seen from the analysis of the six literacy and numeracy indicators.